The Evaluating the Effectiveness of Role-Playing in Enhancing Fourth Graders’ Mastery of Decimal Numbers in Mathematics - Elly Sukmanasa; Indirwan; Munani Salwa; Nana Wahyuni (MASI Mandiri Edukasi, 2025)
In primary school mathematics, inadequate teaching methods remain a persistent challenge that negatively impacts students’ learning outcomes. This quasi-experimental study aimed to evaluate the effectiveness of the role-playing method in improving fourth-grade students' understanding of decimal numbers at SDN Empang 2. The study involved two groups: an experimental group taught using role-play and a control group taught through conventional instruction. Fifty-three students participated, with 26 in the experimental and 27 in the control group. Data were collected using post-test scores and analyzed using an independent t-test. The results showed a statistically significant difference in learning outcomes, with the experimental group achieving a higher mean score (M = 69.69) than the control group (M = 63.85) and a p-value of 0.009 (p < 0.05). These findings indicate that role-playing significantly enhances students’ conceptual understanding and performance in mathematics. The study contributes to the growing research on interactive teaching methods and suggests that role-playing can be an effective pedagogical tool in primary mathematics instruction.